2001
DOI: 10.1002/1521-3773(20010401)40:7<1288::aid-anie1288>3.0.co;2-6
|View full text |Cite
|
Sign up to set email alerts
|

Copper(I) Carbenes: The Synthesis of Active Intermediates in Copper-Catalyzed Cyclopropanation

Abstract: A tailor‐made copper ethylene complex was used to prepare solutions of highly reactive copper(I) carbene complexes of the d10‐ML3 type which are active in olefin cyclopropanation and have been characterized unambigously in situ [Eq. (1)]. Electronic and structural features of this novel class of compounds were determined by NMR spectroscopy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
80
0
1

Year Published

2001
2001
2011
2011

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 138 publications
(85 citation statements)
references
References 17 publications
4
80
0
1
Order By: Relevance
“…An extensive study on the importance of the nature of the support has been recently reported, confirming the need of having a lamellar anionic support to observe such surface 55 confinement effects. 10 A simple model has been proposed to explain those results, taking into account the known cyclopropanation reaction mechanism [11][12][13][14][15][16][17][18][19][20] and the strong ionpair interaction between the key copper-carbene intermediate and the support surface, as well as the steric constraints of the 60 catalytic complex. From that model we proposed the synthesis of chiral ligands without C 2 symmetry as a method to enhance the surface-complex proximity and hence the support-complex interaction, allowing the surface to effectively shield one face of the complex.…”
Section: Consequence the Isomer Cis-(1s2r) (4s) Was Preferably Obtamentioning
confidence: 99%
“…An extensive study on the importance of the nature of the support has been recently reported, confirming the need of having a lamellar anionic support to observe such surface 55 confinement effects. 10 A simple model has been proposed to explain those results, taking into account the known cyclopropanation reaction mechanism [11][12][13][14][15][16][17][18][19][20] and the strong ionpair interaction between the key copper-carbene intermediate and the support surface, as well as the steric constraints of the 60 catalytic complex. From that model we proposed the synthesis of chiral ligands without C 2 symmetry as a method to enhance the surface-complex proximity and hence the support-complex interaction, allowing the surface to effectively shield one face of the complex.…”
Section: Consequence the Isomer Cis-(1s2r) (4s) Was Preferably Obtamentioning
confidence: 99%
“…The first such example was reported by Straub and Hofmann in 2001 and assigned using spectroscopic data. 4 Warren and co-workers later reported X-ray structural data for a b-diketiminato CuQCPh 2 complex. 5 Both of these systems mediate catalytic cyclopropanation reactions and employ diazoalkane precursors to generate the carbenes of interest.…”
Section: -Azine Adductmentioning
confidence: 99%
“…6 In this paper, we describe the utility of the bulky bis(phosphino)borate ligand 7 (4). The X-ray crystal structures of complexes 2 and 3, which are related by a proton transfer, are shown in Fig.…”
Section: -Azine Adductmentioning
confidence: 99%
“…All deuterated solvents were sparged with nitrogen, dried over activated 4A molecular sieves and stored under nitrogen. 1 H, 13 C, and 31 P NMR spectra were recorded on a Mercury Varian 300 MHz spectrometer (300, 121.5, and 75.4 MHz, respectively) at 25°C unless otherwise noted. 1 H and 13 C NMR spectra were indirectly referenced to TMS using residual solvent signals as internal standards, while 31 P Table 9 Bond distances (Å ) and angles (°) in 7…”
Section: General Experimental Detailsmentioning
confidence: 99%
“…A transient copper carbene has been identified via time-resolved FTIR spectroscopy upon addition of N 2 CHCO 2 Me to a cationic bis(oxazoline) Cu(I) precatalyst [12]. Employing a neutral Cu(I) complex featuring the strongly donating iminophosphanimide ligand, Hofmann demonstrated that ½Bu t 2 PðNSiMe 3 Þ 2 -j 2 N CuðethyleneÞ reacts with N 2 C(Ph)(C(O)OMe) to give a mixture in which the carbene ½Bu t 2 PðNSiMe 3 Þ 2 -j 2 N Cu@CðPhÞðCðOÞOMeÞ could be identified by low temperature 1 H, 13 C, and 31 P NMR spectroscopy [13]. Moreover, the presence of two inequivalent Bu t groups indicated that the carbene is orthogonal to the backbone of the bidentate N,N-donor ligand.…”
Section: Introductionmentioning
confidence: 99%